Occupational Integration Training in Translation - Torres-Hostench, Olga (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2012)
This article presents the research carried out at the Faculty of Translation and Interpreting at the Universitat Autònoma de Barcelona (Spain) to evaluate how prepared its postgraduates were for employment. First, students were given an initial test to evaluate their competences related to knowledge, skills and attitudes with regard to occupational integration. Next, an improvement program was designed accordingly, implemented and evaluated. Finally, a posttest was given and we compared the results of the pretest and the posttest. The research suggested that there was a need to incorporate into master’s and postgraduate courses not only content on knowledge of the translation market and the profession but also content to help students develop specific skills and attitudes for finding a job in translation. This research may interest translation course designers and lecturers, who may want to consider including employment programs in translation courses.